Optimization of turbocharger performance on MV magnanimous through planned maintenance under the total productive maintenance (TPM) framework - Sarifuddin Sarifuddin; Zulkani Sinaga (Jurnal Polimesin, 2025)
The turbocharger is a critical component of marine diesel engines, playing a vital role in enhancing air intake pressure and combustion efficiency. This study aims to evaluate the performance degradation of the turbocharger installed on the main engine of Vessel Magnanimous and to implement a structured maintenance strategy to restore its functionality. The research adopts a field-based Research and Development (RD) approach over a 14-month marine engineering practice period. Primary data were obtained through direct observation, operational logbooks, and technical inspections before and after the overhaul and air filter cleaning procedures. The results show a significant performance recovery: exhaust gas temperature increased from 440/400°C to 450/420°C, scavenge air pressure rose from 0.18 MPa to 0.27 MPa, and turbo blower speed returned to 25000 rpm. These improvements reflect the effectiveness of planned maintenance, a core pillar of the Total Productive Maintenance (TPM) framework. Moreover, the restored turbocharger performance contributed to improved combustion efficiency and system reliability, supporting the vessel’s operational productivity. The study concludes that integrating technical repair with TPM-based maintenance can enhance the overall effectiveness of marine engine systems.